Determinants influencing non-trade union membership decision: case of civil servants in Ministry of Works, Malaysia / Hamidah Md Yusop, Khaireyham Khamis and Irwan Shahrezza Mohd Razali - Md Yusop, Hamidah; Khamis, Khaireyham; Mohd Razali, Irwan Shahrezza (Arshad Ayub Graduate Business School, 2018)
Trade union membership is imperative to assess the strength of a trade union. Therefore, this study was conducted to determine factors influencing trade union membership decision among non-union members in Ministry of Works (MoW), Malaysia. In MoW, they have several trade unions and employee representatives under Majlis Bersama Jabatan (The Joint Departmental Council, MBJ) that will get together and discuss matters pertaining to employees in MoW. The union leaders’ concern are with low union membership in most of the establishments. This is in line with the data provided by The Department of Trade Union Affairs that shows declining members in trade unions for public sector. This study aimed to examine the relationship between independent variables and dependant variable and to identify the factors that influence non-trade union member’s membership decision in MoW. The study also was to analyse the current trend of trade union participation in MoW through identified its strengths, weaknesses, threats and opportunities which will be later developed into strategies and recommendations. This study involved union and non-union members, who are the employees from three departments under MoW. SPSS was used in statistical analysis to analyse the demographic profiles as well as independent variables and dependant variable which included frequency analysis, reliability analysis, descriptive analysis, Pearson’s correlation and regression analysis. The findings indicated three out of four independent variables are significantly correlated and also the predictors on dependant variable. The three independent variables are union leadership, union effectiveness and union commitment have significant influence on non-trade union membership decision in MoW. Thus, the union leader and committees should focus on these three factors to increase trade union membership in MoW.